A 26-year-old female with metastatic primary gastrointestinal malignancy presenting as menorrhagia - Khan, Maliha; Bhatti, Ravinder Pal; Mukherjee, Sarbajit; Ali, Alaa M.; Gilman, Alan D.; Mirrakhimov, Aibek E.; Iroegbu, Nkemakolam (Journal of Gastrointestinal Oncology; Vol 6, No 2 (April 13, 2015): Journal of Gastrointestinal Oncology, 2014)
Krukenberg tumor is a metastatic malignant tumor of the ovary arising from a wide variety of primary sources, with the stomach being the most common. The presenting symptoms are non-specific and the primary source is often un-identified. Here, we describe a case of a 26-year-old Hispanic gravida 4, para 3 female who presented to our hospital with dysuria, pelvic pain and irregular, heavy menstrual cycles for three months duration. An endometrial biopsy was suggestive of carcinosarcoma. The patient underwent debulking surgery with partial cystectomy and bladder repair. A week later, she presented with hematemesis and an endoscopic biopsy revealed a diagnosis of poorly differentiated gastric adenocarcinoma. The tissue specimen obtained during the initial surgery was identified as Krukenberg tumor. The patient underwent adjuvant chemotherapy with FOLFOX along with gastrectomy with intraperitoneal chemotherapy.